EXPLORATION OF POTENT ACTINOBACTERIUM NOCARDIOPSIS HALOTOLERANS VJPR-2 ISOLATED FROM MANGROVE HABITATS - Naradala, Prasada Rao; VIJAYALAKSHMI MUVVA,; Mangamuri, Ushakiranmayi; Kavi Kishor Pb, (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: This study was aimed at isolation and identification of potent bioactive metabolite producing actinobacterial strain VJPR-2 isolated from the mangrove ecosystem of Nizampatnam, Andhra Pradesh, India. Methods: Soil sediments collected were subjected to pre-treatment with CaCO , and actinobacterial strains were isolated using selective media. The screening of the isolated strains was carried out and the potent bioactive metabolite producing strain was designated as VJPR-2. An identification of the strain was carried out by employing polyphasic approach including morphological, cultural, physiological, biochemical, and phylogenetic analysis of 16S rRNA gene sequence. Antimicrobial potency of the isolate was tested against bacterial and fungal pathogens. 3 Results: The strain VJPR-2 was identified as Nocardiopsis halotolerans by morphological, cultural, physiological, and biochemical studies along with 16S rRNA gene sequence analysis. The rRNA sequence was deposited in the NCBI GenBank with the accession number KP313613. The strain exhibited antimicrobial activities against Gram-positive as well as Gram-negative bacteria and fungi. Conclusion: Actinobacterium strain N. halotolerans VJPR-2 having good antimicrobial potential was identified from the 16 strains isolated from the sediment samples of Nizampatnam mangrove ecosystem using CaCO based approach. The present study reveals the isolation, identification and biological evaluation of the bioactive metabolites produced by strain VJPR-2. 3 Keywords: Mangrove ecosystem, Nocardiopsis halotolerans VJPR-2, Polyphasic approach, Bioactive metabolites.